Evaluation of Day Fines in Maricopa County, Arizona, 1991-1993 - Turner, Susan ([Verlag nicht ermittelbar], 1999)
This study sought to evaluate how well day fines work as an intermediate sanction. Day fines are a structured approach to imposing fines that considers both the offender's ability to pay and the severity of the offense. The program involves two steps: (1) a determination of the number of fine units for an offense, based on the severity of the offense, and (2) a valuation of fine units, based on the offender's net daily income, hence the name "day fines". While four jurisdictions participated in the day fines evaluation, only the site in Maricopa County, Arizona, was structured in such a way to allow for a quasi-experimental research design. Therefore, this collection only contains data from the Financial Assessment Related to Employability (FARE) day fines program in Maricopa County. The FARE program was started in 1991 and targeted felony offenders with little need for supervision or treatment -- in other words, the low risk-low need defendant. The intent of the program was to draw clients from the population of offenders who would traditionally receive routine probation, thus serving as an intermediate sanction between routine and summary probation. The major research strategy was to consider the FARE-sentenced offenders as the experimental group and to construct a similar comparison group out of the offenders sentenced by non-day fines judges. The design involved three major steps: (1) identification of 1991 and 1992 defendants who received a FARE sentence, (2) screening of sentenced defendants in non-FARE courts using FARE eligibility criteria to match the FARE participants, and (3) coding background and 12-month follow-up information for both FARE and comparison group offenders from probation and clerk files to record background information, monetary payments, and any technical violations and arrests occurring during the 12-month follow-up period. Variables in Part 1, Fines Paid Data, include the total amount of the fine and how much of the fine was applied to probation fees, reimbursement, restitution, and victim compensation. Part 2, Official Records Data, contains background information such as arrest history, marital status, education, drug use, and drug treatment. Additional information includes current arrest, recommended sentence, disposition, sentence imposed, employment and income, and risk/needs assessment. Six- and 12-month reviews collected data on supervisory status, technical violations, new arrests, payment enforcement, and payment term revisions.